Variability in coral‐reconstructed sea surface salinity between the northern and southern lombok strait linked to East Asian winter monsoon mean state reversals - Wiguna, A. A. (2019)
The Indonesian throughflow (ITF) impacts heat and buoyancy transport from the Pacific Ocean to the Indian Ocean, influencing air‐sea heat exchange and Indo‐Pacific climate. Nearly 80% of the total 15 sverdrups (1 Sv = 106 m3/s) of ITF water moves through the Makassar Strait in the western Indonesian seas, with ~20% of total ITF transport subsequently entering the Indian Ocean through the Lombok Strait. During the East Asian winter monsoon (EAWM), buoyant South China Sea (SCS) waters obstruct southward surface ITF transport in the Makassar Strait, likely impacting surface variability throughout the Lombok Strait. Here we present two subannually resolved, multicentury records of coral‐reconstructed sea surface salinity (SSS) from the northern (110 years) and southern Lombok Strait (193 years). Differences in boreal winter (January–March) SSS variability between the two sites suggest the influence of multiple source waters. Instrumental and reconstructed temperature‐salinity (T‐S) relationships indicate that SCS surface waters dominate the northern Lombok Strait, while Indian Ocean surface waters instead dominate the southern Lombok Strait before 1960. These dissimilarities are likely due to changes in monsoon‐driven surface water advection. At the northern site, the EAWM consistently influences SSS variability. The EAWM influence at the southern site, however, reverses in direction (inverse to direct) coincidentally with a transition from a positive (strong) to negative (weak) EAWM state in 1960. Our records collectively reveal that changes in the strength and state of the EAWM impact Lombok Strait surface water circulation, likely interacting with southward ITF transport and thus Indo‐Pacific climate.